2016
DOI: 10.1007/s40069-016-0175-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Temperature on Mechanical Properties of Limestone, Quartzite and Granite Concrete

Abstract: Although concrete is a noncombustible material, high temperatures such as those experienced during a fire have a negative effect on the mechanical properties. This paper studies the effect of elevated temperatures on the mechanical properties of limestone, quartzite and granite concrete. Samples from three different concrete mixes with limestone, quartzite and granite coarse aggregates were prepared. The test samples were subjected to temperatures ranging from 25 to 650°C for a duration of 2 h. Mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(66 citation statements)
references
References 26 publications
0
66
0
Order By: Relevance
“…Moreover, the rough angular surfaces of aggregates (which improve the physical cement paste-aggregate bond), as well as the presence of reactive silica (which improves chemical bonds), are desirable features of aggregates [ 9 ]. In general, aggregates usually remain stable up to 500–600 °C, although some siliceous aggregates, such as flint [ 9 , 11 ], are stable only up to 300–350 °C [ 2 , 12 ]. It has been reported that siliceous aggregates (i.e., quartzite, granite), have worse thermal resistance than carbonatic aggregates (such as limestone or dolomite) [ 3 , 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the rough angular surfaces of aggregates (which improve the physical cement paste-aggregate bond), as well as the presence of reactive silica (which improves chemical bonds), are desirable features of aggregates [ 9 ]. In general, aggregates usually remain stable up to 500–600 °C, although some siliceous aggregates, such as flint [ 9 , 11 ], are stable only up to 300–350 °C [ 2 , 12 ]. It has been reported that siliceous aggregates (i.e., quartzite, granite), have worse thermal resistance than carbonatic aggregates (such as limestone or dolomite) [ 3 , 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A post-fire compressive strength factor of 0.45 is recommended in the general rules for the structural fire design of Eurocode 2 [ 73 ] for normal-weight concrete with siliceous aggregates exposed to 600 °C. The reduction in compressive strength occurs due to the degradation of C-S-H after 400 °C [ 74 ] and the decomposition of Portlandite between 200 °C and 600 °C [ 75 , 76 , 77 ], which is considered the limit for the integrity of concrete mechanical properties. The results of Figure 11 demonstrate that only the concretes with the incorporation of PP fibers and plastic waste were able to reach the 0.45 factor, with the higher residual compressive strengths obtained with the incorporation of 6 kg/m 3 of polymeric addition.…”
Section: Resultsmentioning
confidence: 99%
“…• φ 150 mm cylinders: Kliszczewicz (2002, 2007), Atahan et al (2011), Bilodeau and Malhotra (1992), Bravo et al (2015a), Carette et al (1993), Casuccio et al (2008), Demir (2009), Dilbas et al (2014), Dossey et al (1994), Etxeberria et al (2007a-b), Evangelista (2014), Evangelista and de Brito (2017), Gomez-Soberon (2002), Martínez-Abella (2004, 2005), González-Fonteboa et al (2011), Gutierrez and Canovas (1995), Hamad and Dawi (2017), Kheder and Al-Windaw (2005), Kliszczewicz and Ajdukiewicz (2002), Koulouris et al (2004), Naik et al (1998), Omary et al (2018), Paul (2011), Pedro et al (2014), Piasta et al (2017), Pul (2008), Remesar et al (2017), Sadati and Khayat (2016), Sivasundaram et al (1989Sivasundaram et al ( , 1991, Tufail et al (2017), Di Maio (2006, 2009); • φ 100 mm cylinders: Aitcin and Mehta (1990) 2014, Iravani (1996), Jin and Li (2003), Khaliq and Taimur (2018), Kim et al (2002), Kou et al (2007) Vogel and Svecova (2012), Yanagi et al (1998), Yang et al (2008),…”
Section: Database Criteriamentioning
confidence: 99%